Teacher Habits And Workload In The Digitalization Of Education - Hilhamsyah, Hilhamsyah; Hidayati, Dian; Imama, Mohammad Luthfi (Universitas Negeri Malang, 2024)
The digitalization of education has brought about significant changes in the roles and responsibilities of teachers. These changes provide new challenges and opportunities for teachers to integrate technology to support their professional work. The digitalization of education requires teachers to use digital technology in all their work, thus changing many teachers' habits and workloads to support their professional work. Therefore, this study aims to uncover teachers' habits and workload in the digitalization of education. This study employed a literature study type of research by identifying topics based on previous research relevant to the objectives. The results of this study reveal that the digitalization of education can provide changes in the habits and workloads of teachers. These habits encompass digitalization in learning, administration, and the development of teachers' digital competence. In addition, the workload of teachers is lighter with digitalization. The results of this study are expected to contribute to the development of teacher competence in the digital era. Abstrak Digitalisasi pendidikan telah memberikan perubahan yang signifikan peran dan tanggung jawab guru. Perubahan ini memberikan tantangan dan peluang baru bagi guru dalam mengintegrasikan teknologi untuk menunjang pekerjaan profesional sebagai seorang guru. Digitalisasi pendidikan mengharuskan guru untuk menggunakan teknologi digital dalam segala pekerjaan, sehingga banyak mengubah kebiasaan dan beban kerja guru untuk mendukung pekerjaan profesionalisme guru. Tujuan penelitian ini adalah untuk mengungkap kebiasaan-kebiasaan guru dan beban kerja guru dalam digitalisasi pendidikan. Penelitian ini menggunakan jenis penelitian studi literatur dengan mengidentifikasi topik penelitian berdasarkan penelitian terdahulu yang relavan dengan tujuan penelitian. Hasil dari penelitian ini yaitu menunjukkan digitalisasi pendidikan mampu memberikan perubahan kebiasaan dan beban kerja guru. Kebiasaan ini mencakup digitalisasi dalam pembelajaran, digitalisasi dalam administratif dan pengembangan kompetensi digital guru. Selain itu beban kerja guru lebih diringankan dengan adanya digitalisasi. Hasil penelitian ini diharapkan dapat memberikan kontribusi bagi pengembangan kompetensi guru di era digital.